Pengaruh Imbangan Tepung Ubi Jalar Ungu (Ipomea batatas L) dan Sari Kedelai (Glycine max L) terhadap Karakteristik Es Krim - Sopianti, Nanda Audina; Khairina, Amila (Jurnal Dimamu, 2024)
Ice cream is a frozen dessert with a lot of milk that everyone likes. One factor determining thePquality of icePcream is the density of ice cream consisting of fat, protein, carbohydrate, vitamins and minerals. The purple sweet potato flour and soybean extract can be added into the dough to improve the density and characteristics of the ice cream as a whole. This researchPhas been carried out to determine the balance of purple sweet potato flour and soybean extract the most appropriate to produce ice cream with the best characteristics. The methPused in this research isPthe experimental method with the Acute Group Project consisting of five treatments of the balance of purple-striped wax and silk sari which are A (35:65:0), B (30:65:5), C (25:65:10), D (20:65:15), dan E (15:65:20). Each treatment was repeated five times. ThePresults showed thatPtreatment B, namely thePaddition of 5 grams of thePpurple sweetPpotato flour to the textkaure, produced the best characteristics of ice cream based on organoleptic tests of color, taste, texture and aroma.